Pleurostomophora richardsiae associated with olive tree and grapevine decline in Southern Brazil - Maria Cristina CANALE; Cristiano NUNES NESI; Bianca FALKENBACH; Cesar HUNHOFF DA SILVA; Eduardo BRUGNARA (Phytopathologia Mediterranea, 2019)
Olive trees showing decline symptoms were reported in an orchard in Santa Catarina, Southern Brazil. The symptoms included foliar browning and leaf drop, dieback of twigs and branches, dark streaks in internal crown wood and necrotic lesions in bark. A grapevine sample exhibiting browning streaks in the vascular tissue of branches, trunk and roots, was also analysed. A Phialophora-like fungus was isolated from symptomatic tissues of both hosts, and monosporic cultures were established. Based on morphology and analysis of ITS, tub2 and tef sequences, the fungus was identified as Pleurostomophora richardsiae. Isolates inoculated onto young nursery olive trees and grapevines produced brown streaking in the wood in most of the inoculated plants. This is the first report of P. richardsiae occurring in olive trees and grapevines in Brazil.